(3fKQ GdOQQ aj GdeMGVQGJs - (3efUhQ Hf GdMSjf GdQGRqj, nCHh nSrYO GdBHj,J (B421 (3g` s ((3CMeO Hf Ydi GdcGJH GdHZOGOi s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg hbjd dg gd ef CLO dGYjH ajg bGd GdPi dGYjH ajg GdPi dGjehJ s
(3BNQgG (B:s
(3acGf ef bUJc eG QCjJ bGd CadG CNHQc HGYLH ef Pdc bdJ Hdi bGd Jdc hGdgd GNJi dCHi hGei hgPg GNJ GdQLd dGHjg hGeg s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B298s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1927s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs